Boosting LiMn2O4 Diffusion Coefficients and Stability via Fe/Mg Doping and MWCNT Synergistically Modulating Microstructure - Natasha Ross; Shane Willenberg; Thando Juqu; Emanuela Carleschi; Bryan P. Doyle (Journal of Nanotechnology)
The dissolution of manganese and its deposition on the anode surface cause poor cycling stability in lithium-ion batteries. To alleviate these issues, this study probes the electrochemical activity of highly crystalline and cation-adjusted lithium manganese oxide (LMO) carbon spinel composite obtained via a modified sol-gel synthesis procedure. The pristine LMO cathode was functionalized with a Fe and Mg alloy and fused with purified multiwalled carbon nanotubes (MWCNTs) to form a catalytically stabilized LiMn1.98Fe0.01Mg0.01O4/MWCNT (LMO-FeMg/MWCNT) framework. High-resolution SEM analysis showed well-dispersed particles in the nanometer size range. The electrochemical characteristics of the novel composite materials yielded favourable electrochemical results with diffusion coefficients of 1.91 × 10−9 cm2·s−1 and 5.83 × 10−10 cm2·s−1 for LMO-FeMg and LMO-FeMg/MWCNT, respectively. This improvement was supported by impedance studies which showed a considerable Rct reduction of 0.27 Ω and 0.71 Ω. The cation stabilized system outperformed the pristine LMO material with specific capacities around 145 mAh·g−1, due to an enhancement in electrochemical activity and structural stability.